2020
DOI: 10.1002/chem.202001654
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Approach to a One‐Pot Electrochemical Wittig Olefination Avoiding the Use of Chemical Reductant or Sacrificial Electrode

Abstract: An unprecedented one‐pot fully electrochemically driven Wittig olefination reaction system without employing a chemical reductant or sacrificial electrode material to regenerate triphenylphosphine (TPP) from triphenylphosphine oxide (TPPO) and base‐free in situ formation of Wittig ylides, is reported. Starting from TPPO, the initial step of the phosphoryl P=O bond activation proceeds through alkylation with RX (R=Me, Et; X=OSO2CF3 (OTf)), affording the corresponding [Ph3POR]+X− salts which undergo efficient el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 68 publications
0
61
0
Order By: Relevance
“…Alternatively, the same electrochemical technology with intermetallics can be applied in non-aqueous solvents to drive the other essential transformations such as regeneration of the triphenylphosphine from triphenylphosphine oxide as well as a one-pot Wittig olefination reaction that presently best driven by noble-metal catalysts. 238 Furthermore, the scope of the intermetallics can easily be extended electrochemical carbon dioxide (CO 2 ) reduction, a promising reaction to mitigate CO 2 emissions, where presently transition metals (in particularly Cu) have been used predominantly to yield high-end multicarbon products. Notably, the intermetallics can also be of special interest for the kinetically sluggish oxygen reduction reaction (ORR), an important cathodic reaction of fuel cell which is presently mediated by the metals, alloys, and carbons, etc.…”
Section: Conclusion and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the same electrochemical technology with intermetallics can be applied in non-aqueous solvents to drive the other essential transformations such as regeneration of the triphenylphosphine from triphenylphosphine oxide as well as a one-pot Wittig olefination reaction that presently best driven by noble-metal catalysts. 238 Furthermore, the scope of the intermetallics can easily be extended electrochemical carbon dioxide (CO 2 ) reduction, a promising reaction to mitigate CO 2 emissions, where presently transition metals (in particularly Cu) have been used predominantly to yield high-end multicarbon products. Notably, the intermetallics can also be of special interest for the kinetically sluggish oxygen reduction reaction (ORR), an important cathodic reaction of fuel cell which is presently mediated by the metals, alloys, and carbons, etc.…”
Section: Conclusion and Challengesmentioning
confidence: 99%
“…Alternatively, the same electrochemical technology with intermetallics can be applied in non-aqueous solvents to drive the other essential transformations such as regeneration of the triphenylphosphine from triphenylphosphine oxide as well as a one-pot Wittig olefination reaction that presently best driven by noble-metal catalysts. 238 …”
Section: Conclusion and Challengesmentioning
confidence: 99%
“…Sevov et al used AlCl 3 and tetralkylammonium salt as additives in which AlCl 3 makes a coordinate bond with oxygen of the "P=O" bond followed by activation of TPPO. [93] Furthermore, an isolable ionic salt could also be prepared from a reaction mixture of TPPO and AlCl 3 . [94] Very similar to Elias' observation, a change in redox peak feature of TPPO was reported by Sevov and confirmed that a 0.33 equivalent of AlCl3 is sufficient to activate the TPPO presumably due to a 1 : 3 stoichiometry of AlCl 3 : TPPO in solution state (Figure 5d).…”
Section: Activation Of "P=o" Bond Of Tppo For Selective Electroreduct...mentioning
confidence: 99%
“…[42] We hoped that the increased reactivity of the Ph 3 As = O might make its reduction compatible with an anodic cyclization in the presence of the required methanol solvent and thereby provide information on the reduction potential needed for such a process. This alternative for Ph 3 P=O was intriguing because Geary and co-workers have demonstrated that Wittig reactions can be conducted with the use of Ph 3 As in place of the Ph 3 P. [43,44] The reduction of Ph 3 As=O was initially paired with the oxidation of veratryl alcohol [Scheme 10, Eq. (a)].…”
Section: Pairing Oxidations With the Reduction Of Ph 3 P = Omentioning
confidence: 99%